Computational Insights Into the Influence of Substitution Groups on the Inclusion Complexation of β-Cyclodextrin - Yan, Xianghua; Wang, Yue; Meng, Tong; Yan, Hui (Frontiers in Chemistry, 2021)
Cyclodextrins (CD) and its derivatives have a good applications prospect in the field of soil remediation, due to their ability to enhance the stability and solubility of low water-soluble compounds by inclusion performance. To investigate the effect of different structural properties of CD and its derivatives on the inclusion complexation, molecular dynamics (MD) simulations were performed on the inclusion complexes formed by three kinds of CD with polycyclic aromatic hydrocarbons (PAHs). Based on neutral β-CD, the other two CDs were modified by introducing substitution groups including 2-hydroxyprohyl (HP) and sulfonated butyl (SBE) functional groups into the ring structure, called HP-CD and SBE-CD. MD results show that PAH can merely enter into the cavity of SBE-βCD from its wide rim. The substitution groups have great effect on the CD structure, which may cause the flipping of the glucose units. However, the substitution groups can also enlarge the hydrophobic cavity volume, resulting in a tight binding with the guest molecules.